Formation and development of the first department of infectious diseases in children in Russia - V. N. Timchenko; G. L. Mikirtichan; T. M. Chernova (Журнал инфектологии, 2014)
80 years marks since the founding of the department of infectious diseases in children of St. Petersburg State Pediatric Medical Academy in 2010. The historical review presented in detail the stages and formation of oldest development in Russia the department of children’s infections. The main directions of infectious diseases and training of specialists in the field of infectious diseases in children presented.